(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
in this article, the oral cavity the specific differences of the mucous membrane from other mucous membranes of the body, the local immunity of the oral cavity, as well as the pathological processes that take place there, how the immune activity against diseases takes place in the oral cavity, and injuries and injuries , to get rid of them, to maintain the health of all organs as much as possible, the recommendations of not to ignore diseases of the oral cavity are stated.